THE AUCTION. - Yurick, Sol (Artforum International)
Focuses on the auction conducted by the organization Digitalized Byzantine Mosesaics (DBM) founded by three former freelance programmers. Aim of the group to sell the petrified womb of the Virgin Mary; Objective of DBM to raise money to develop an art program designed to generate multi-dimensional variations of any phantasmagoric theme; Ownership by DBM of a source code for a computer operating system; Services hired to realize the auction event and its details; Coverage of the bidding process between the primary bidders; Impact of the auction results on the stock market on October 19, 1987.